The forms and purpose of work undertaken by family carers of people living in a care home with a cognitive impairment across a care trajectory - Fawn Harrad-Hyde; Christina Faull; Linda Birt (PLoS ONE, 2026)
When older people move into care homes, family carers continue to provide unpaid support and care but little is known about how the types of work they undertake and how work changes over time. Drawing on data collected from semi-structured interviews with 29 family carers, we describe six forms of work carers undertook across the care trajectory. These were body work, comfort work, information work, coordination work, safety work and biography work. Whilst the nature of each form of work changed over time, carers undertook work across all phases of the care trajectory. This work was purposeful, undertaken to maintain the care recipient’s dignity, health, wellbeing and functional and cognitive abilities.